INOVASI PENDIDIKAN MELALUI PENDEKATAN KEWIRAUSAHAAN BERBASIS TEACHERPRENEUR - Endik Suryanto; Amrozi Khamidi; Dewie Tri Wijayati Wardoyo (STKIP Pesisir Selatan, 2026)
This study examines the concept of entrepreneurship from theoretical, historical, and practical perspectives, with an emphasis on its application in education. The discussion begins with the development of entrepreneurship from prehistoric times, the agricultural revolution, the Middle Ages, the industrial revolution, and the digital era marked by technological advances and globalization. The main focus of this study is the concept of teacherpreneurship, which is the combination of the role of teachers as educators and entrepreneurs oriented towards creating educational innovation. Teachers with a teacherpreneurial spirit are expected not only to carry out their teaching function but also to act as agents of change through the development of ethical and sustainable educational businesses. This study uses a qualitative method with a literature study approach, collecting data from books, journals, scientific articles, and relevant digital sources regarding entrepreneurship. The results of the analysis indicate that a comprehensive understanding of the theory and concept of entrepreneurship is crucial for implementation in the world of education, in order to create an adaptive, creative, and competitive learning system. Furthermore, entrepreneurship is understood broadly, starting from its definition, history, and multidisciplinary theories that emphasize the strategic role of entrepreneurs in creating value, innovation, and economic growth.